The origin of unique diversity in deglaciated areas: traces of Pleistocene processes in north-European endemics from the Galium pusillum polyploid complex (Rubiaceae) - Kolář, Filip; Píšová, Soňa; Záveská, Eliška; Fér, Tomáš; Weiser, Martin; Ehrendorfer, Friedrich; Suda, Jan (Molecular ecology, 2015)
The role of glacial oscillations in shaping plant diversity has been only rarely addressed in endemics of formerly glaciated areas. The Galium pusillum group represents a rare example of an ecologically diverse and ploidy-variable species complex that exhibits substantial diversity in deglaciated northern Europe. Using AFLP and plastid and nuclear DNA sequences of 67 populations from northern, central, and western Europe with known ecological preferences, we elucidate the evolutionary history of lineages restricted to deglaciated areas and identify the eco-geographic partitioning of their genetic variation. We reveal three distinct endemic northern lineages: (i) diploids from southern Sweden + the British Isles, (ii) tetraploids from southern Scandinavia and the British Isles that show signs of ancient hybridization between the first lineage and populations from unglaciated central Europe, and (iii) tetraploids from Iceland + central Norway. Available evidence supports a stepwise differentiation of these three lineages that started at least before the last glacial maximum by processes of genome duplication, interlineage hybridization and/or allopatric evolution in distinct periglacial refugia. We reject the hypothesis of more recent postglacial speciation. Ecological characteristics of the populations under study only partly reflect genetic variation and suggest broad niches of postglacial colonizers. Despite their largely allopatric modern distributions, the north-European lineages of the G. pusillum group do not show signs of rapid postglacial divergence, in contrast to most other northern endemics. Our study suggests that plants inhabiting deglaciated areas outside the Arctic may exhibit very different evolutionary histories compared with their more thoroughly investigated high-arctic counterparts.
Keywords: Amplified Fragment Length Polymorphism Analysis; Ploidies; Švédsko; United Kingdom; DNA, Plant; angiosperms; Genetic Speciation; phylogeography; Scandinavian and Nordic Countries; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; Molecular Sequence Data; DNA chloroplastová; Spojené království; ploidie; Island; svízel; Genetic Variation; systematics; Genetics, Population; molekulární sekvence - údaje; hybridization; Sweden; Iceland; DNA rostlinná; DNA, Chloroplast; Sequence Analysis, DNA; vznik druhů (genetika); Skandinávie a severské státy; Galium; sekvenční analýza DNA; genetická variace; populační genetika